Predictive Analytics Decision Tree: Mapping Patient Risk to Targeted Interventions in Chronic Disease Management - Parameshwarappa, Naveen (International Journal of Computing and Engineering, 2025)
Predictive analytics is revolutionizing chronic disease management by enabling healthcare organizations to shift from reactive to proactive care models. This scholarly article explores how advanced risk stratification methodologies and readmission prediction models are transforming resource allocation and improving patient outcomes across healthcare settings. The article discusses the evolution from basic rules-based systems to sophisticated machine learning algorithms that incorporate social determinants of health alongside clinical variables. It details how real-time alert systems integrated into clinical workflows can identify high-risk patients before clinical deterioration becomes evident, allowing for timely interventions. The article also analyzes the technical architecture required for embedding predictive analytics into care management platforms, supporting quality metrics through automated care gap identification, and optimizing resource allocation for care teams. Cost-benefit analyses demonstrate compelling returns on investment across various healthcare contexts while addressing ethical considerations regarding algorithmic bias and privacy. Finally, the article examines emerging technologies in predictive healthcare analytics and provides a structured implementation roadmap that addresses both technical requirements and organizational change management necessary for successful adoption.